Establishment of Children's Moral (Case Study of Temporary Suspension of Entertainment Program Dahsyat by Indonesia Broadcasting Commission) - Lakna Tulas'un; Isti Winarni (INJECT (Interdisciplinary Journal of Communication), 2021)
Many media companies in Indonesia intentionally or unintentionally produced program that do not educate people, especially the children by ignoring moral value without adhering to ethics of media broadcasting which is regulated by Indonesian Broadcasting Commission (KPI), so they neglected the regulations.  They only broadcasted top rated entertainment program for financial profit without considering the effects towards the society.  Media no longer educate the people, but trapped in the logic of market. The purpose of the research is to find out media broadcasting ethics in establishing children’s moral in ‘Temporary Suspension of Entertainment Program Dahsyat by Indonesian Broadcasting Commission (KPI)’ which was analyzed by Bandura’s Social Learning Theory and Agenda Setting Communication Theory by Mc Combs and Shaw. The advantage of the research is to find out the application of the broadcasting ethics in a media. Research method used in this research eas qualitative methods.  The final result of the case analysis which was elaborated by using those theories are: 1) The case which was analyzed by Bandura learning theory according to Broadcasting Code of Conduct (P3) and Broadcast Program Standards regulated by Indonesian Broadcasting Commission (KPI), entertainment program broadcasted by RCTI “Dahsyat”  breaks the rules because the program did not educate and establish moral of the children, therefore Indonesian Broadcasting Commission (KPI) suspended the program for three days as punishment.  2.) The case analyzed by Agenda Setting Communication Theory by Mc Combs and Shaw (1972), entertainment program broadcasted by RCTI “Dahsyat” was only for entertainment purpose, therefore it was considered unimportant. However, it became important from the audience point of view because media considered it important as well as the theories.